2022
DOI: 10.1002/cncr.34348
|View full text |Cite
|
Sign up to set email alerts
|

Differential prognostic effect of systemic inflammation in patients with non–small cell lung cancer treated with immunotherapy or chemotherapy: A post hoc analysis of the phase 3OAKtrial

Abstract: BACKGROUND:A proinflammatory diathesis, as measured by the neutrophil to lymphocyte ratio (NLR), heralds an adverse disease course for non-small cell lung cancer (NSCLC). METHODS: This post hoc analysis used data from the phase 3 OAK trial (NCT02008227), which randomized previously treated patients with NSCLC to atezolizumab or docetaxel. The main objective was assessing the differential impact of the pretreatment NLR on overall survival according to the treatment modality. In addition, patients' genomic chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The negative prognostic value of NLR has been confirmed in several tumour types [17][18] , including the aUC treated with either immunotherapy 6,8,9 or chemotherapy [19][20] and other urological cancers treated with immunotherapy 21 . Recently, NLR was indicated as a possible predictive factor for advanced non-small-cell lung cancer treated with single-agent immunotherapy after progression to firstline chemotherapy 22 . In our previous analysis of the Italian SAUL patient cohort 8 , we found that the SII, with the receiving operating curve (ROC)-derived cut-off of 884, performed slightly better than NLR in terms of prognostic accuracy, which was confirmed in the current analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The negative prognostic value of NLR has been confirmed in several tumour types [17][18] , including the aUC treated with either immunotherapy 6,8,9 or chemotherapy [19][20] and other urological cancers treated with immunotherapy 21 . Recently, NLR was indicated as a possible predictive factor for advanced non-small-cell lung cancer treated with single-agent immunotherapy after progression to firstline chemotherapy 22 . In our previous analysis of the Italian SAUL patient cohort 8 , we found that the SII, with the receiving operating curve (ROC)-derived cut-off of 884, performed slightly better than NLR in terms of prognostic accuracy, which was confirmed in the current analysis.…”
Section: Discussionmentioning
confidence: 99%
“…High post-treatment NLR has also been associated with poor survival outcomes in cancer patients treated with immune checkpoint inhibitors ( 162 ). Combining NLR assessment with other biomarkers of response to immune checkpoint inhibitors, such as PD-L1 expression, tumor mutation burden, or lymphocyte infiltration, has been shown to provide additional predictive power in identifying patients who respond to treatment ( 164 169 ). Finally, in meta-analyses, lower baseline NLR was significantly associated with immune-related adverse events (irAEs) resulting from the use of immune checkpoint inhibitors in cancer patients ( 170 , 171 ).…”
Section: A High Neutrophil-to-lymphocyte Ratio Is An Independent Prog...mentioning
confidence: 99%
“…In patients with previously treated advanced NSCLC, the POPLAR and OAK randomized clinical trials established the superiority of atezolizumab, a PD-L1 inhibitor, over standard chemotherapy with docetaxel, leading to the approval of the PD-L1 inhibitor as a second-line treatment option after progression to first-line platinum-based chemotherapy, regardless of PD-L1 expression levels [124,125]. A post hoc analysis of these two studies was focused on the role of NLR as an additional biomarker other than PD-L1 expression [126]. The study found that the combination of the NLR and PD-L1 expression was more accurate in predicting the outcomes to atezolizumab compared to the single evaluation of PD-L1 expression.…”
Section: Pd-l1 Expression and Tumor-infiltrating Lymphocytesmentioning
confidence: 99%